Synthesis of a New Type of 5-Heteroaryl-3-Mercapto- 4-Amino-1,2,4-Triazoles and their Derivatives - Ratnakar, A.; Buchi Reddy, R.; Chandra Mouli, G.V.P.; D. Reddy, Y. (Asian Journal of Chemistry, 2010)
A series of 4-amino-3-substiuted mercapto-5-aryl/heteroaryl-1,2,4-triazoles have been prepared by reaction of the corresponding 1,3,4-oxadiazoles with hydrazine hydrate in alcohol. The compounds have been screened for their antimicrobial properties.